2022
DOI: 10.1111/ceo.14045
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The association between keratoconus and allergic eye diseases: A systematic review and meta‐analysis

Abstract: Background: To investigate association between keratoconus and allergic eye diseases, eye rubbing, and atopy.Methods: PubMed, Web of Science, Scopus, and Cochrane were searched for relevant published studies from inception to April 2021 without restrictions or filters. We included case-control, cohort, and cross-sectional studies that investigated eye allergy, atopy, or eye rubbing as possible risk factors for KC. Two authors independently screened all titles and abstracts against predefined inclusion and excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
(126 reference statements)
2
21
0
Order By: Relevance
“…The association between atopy and KC has been reported since the beginning of the 20th century, and many conflicting reports have been published (23,24). The present study showed that atopy was a risk factor for KC, consistent with a study by Millodot et al (23) In contrast, no significant association has been demonstrated between atopy and KC in other studies (9,14,24). The variations in definitions, populations heterogeneity, and duration of atopy may arise from the conflicting results of different studies (25).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The association between atopy and KC has been reported since the beginning of the 20th century, and many conflicting reports have been published (23,24). The present study showed that atopy was a risk factor for KC, consistent with a study by Millodot et al (23) In contrast, no significant association has been demonstrated between atopy and KC in other studies (9,14,24). The variations in definitions, populations heterogeneity, and duration of atopy may arise from the conflicting results of different studies (25).…”
Section: Discussionsupporting
confidence: 92%
“…Advising KC patients to stop eye rubbing has been a common recommendation, and the association between eye rubbing and KC has been widely studied in the past (12)(13)(14)(15). Some cases of unilateral KC have been reported to have developed in response to a unilateral habit of eye rubbing, which indicated that there might exist a strong association between eye rubbing and KC (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We congratulate Seth et al 4 for the publication of “The association between keratoconus and allergic eye diseases: A systematic review and Meta‐analysis” in this issue of Clinical and Experimental Ophthalmology . The authors screened 361 titles and abstracts to include 15 observational studies (10 case–control, 5 cross‐sectional) with 708 225 participants (20 336 of them had keratoconus) in quantitative meta‐analyses; and 7 studies (6 cross‐sectional, 1 basic science) with 899 participants (709 of them had keratoconus) in descriptive analyses.…”
mentioning
confidence: 99%